Die Rechtfertigung der Gier und die Finanzkrise - Zbigniew Waleszczuk (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2013)
The aim of this article is at first to answer the question of greed (the justification of this “virtue” in the modern economic system), which is meant, in the light of Christian social ethics to be the primary cause of the present economic crisis. In the three steps of catholic social teaching (see, judge, act) we want to interpret the signs of our time (present age problems) in the light of the Gospel (and the teaching and tradition of the Church). The relevant question we have to pose in our statement is: Why does catholic social teaching, in opposite to the modern view of economic and political science, object to a justification of greed? The third (practical) step of our explanations we can paraphrase with the question: what shall we do? The focusing on institutional reforms, the belief in arrangements which exclusively accentuate sociological key aspects and believe in changes of structures (in education, politics, economics and welfare) led not only to market crisis, but also to a crisis of culture. If the human being in his/her deepest dimension (the ecology of person) is suffering, then the Church cannot remain silent, because its mission and way is the person. Not until we – like king Solomon – turn to God and ask for help and the ability to judge between good and evil, just and unjust, shall we find a safe basis to lead us out of despair and disorientation into a more humane civilization of humanity and solidarity.